Can flecainide totally eliminate bidirectional ventricular tachycardia in pediatric patients with Andersen-Tawil syndrome? - Yakup Ergül; Senem Özgür; Sertaç Hanedan Onan; Volkan Tuzcu (KARE Publishing, 2018)
Andersen-Tawil syndrome (ATS) is a disorder that causes episodes of muscle weakness (periodic paralysis), changes in heart rhythm, and developmental abnormalities. QT prolongation and ventricular arrhythmias, including bidirectional ventricular tachycardia (VT) and polymorphic VT, may occur. About 60% of all cases of the disorder are caused by mutations in the KCNJ2 gene. A 13-year-old female patient was referred for frequent premature ventricular contractions. Suspicion of ATS due to dysmorphic findings, electrocardiogram changes, and periodic muscle weakness was genetically confirmed. Beta-blocker therapy was initiated as a first-line treatment for bidirectional VT and frequent polymorphic premature ventricular contractions. Despite proper treatment, the VT attacks were not brought under control. Flecainide was added to the treatment regime. The number of premature ventricular contractions was dramatically reduced with flecainide and the VT attacks completely disappeared. This patient is a rare example of ATS in our country. This article provides a description of successful management of rhythm disturbance in a patient with ATS